2019
DOI: 10.1149/2.0382001jss
|View full text |Cite
|
Sign up to set email alerts
|

Review—Defect-Tolerant Luminescent Properties of Low InN Mole Fraction InxGa1-xN Quantum Wells under the Presence of Polarization Fields

Abstract: Different from the case of GaN or AlGaN alloys, the near-band-edge (NBE) emission of quantum wells (QWs) and even epilayers of InxGa1-xN alloys of low InN mole fractions (x) exhibits high quantum-efficiency (QE) against the presence of threading dislocations (TDs) as high as 109 cm−2. Accordingly InxGa1-xN alloys are exclusively used as an active region of green to ultraviolet light-emitting diodes (LEDs) and laser diodes, as well as the heart of white LEDs. Here, current understandings on the emission mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…It was confirmed that the H1 trap in the depletion layer were completely filled by holes under application of U , P 24) i.e., the H1 traps change to the hole-occupied state from the p + -n junction to the deep region (>1 μm), despite the hole diffusion length in n-type GaN of 10 1 to 10 2 nm [35][36][37] because the electron capture cross section of the H1 trap ( -10 22 to -10 21 cm 2 24,38,39) ) is sufficiently smaller than the hole capture cross section ( -10 14 to -10 13 cm 2 24,38,39) ). In sub-E g -light ICTS, the relationship between ÑT and N T is expressed as:…”
mentioning
confidence: 90%
“…It was confirmed that the H1 trap in the depletion layer were completely filled by holes under application of U , P 24) i.e., the H1 traps change to the hole-occupied state from the p + -n junction to the deep region (>1 μm), despite the hole diffusion length in n-type GaN of 10 1 to 10 2 nm [35][36][37] because the electron capture cross section of the H1 trap ( -10 22 to -10 21 cm 2 24,38,39) ) is sufficiently smaller than the hole capture cross section ( -10 14 to -10 13 cm 2 24,38,39) ). In sub-E g -light ICTS, the relationship between ÑT and N T is expressed as:…”
mentioning
confidence: 90%
“…11,12 Similarly, while other III-nitride semiconductors like AlN, InN, and their alloys, alongside rare-earth active luminescent materials, have been explored extensively in various optoelectronic devices, 13−15 they often fall short in terms of luminescence efficiency. 16 In the oxide class of materials, ZnO has a nearly comparable bandgap (∼3.37 eV) as GaN (∼3.4 eV), but a higher E b of ∼60 meV 10 presents itself as an alternative WBG semiconductor with enhanced luminescence efficiency. Nevertheless, the challenge persists in achieving high-quality p-type ZnO, 17 thereby limiting its applications and driving the search for superior alternative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Wide-bandgap (WBG) semiconductors have garnered significant interest owing to their diverse functionalities and widespread technological applications in high-power electronics, light-emitting diodes, solid-state semiconducting lasers, transducers, , and as host materials for single-photon emitters . A critical characteristic of WBG semiconducting materials is their exciton binding energy (BE) (E b ), which plays a pivotal role in determining their luminescence efficiency. , Gallium nitride (GaN), a ubiquitous and industrially vital LED material, exhibits a modest E b of only 26 meV, limiting its luminescence efficiency. , Similarly, while other III-nitride semiconductors like AlN, InN, and their alloys, alongside rare-earth active luminescent materials, have been explored extensively in various optoelectronic devices, they often fall short in terms of luminescence efficiency . In the oxide class of materials, ZnO has a nearly comparable bandgap (∼3.37 eV) as GaN (∼3.4 eV), but a higher E b of ∼60 meV presents itself as an alternative WBG semiconductor with enhanced luminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][64][65][66] To explain these ameliorative Si-doping effects in the wells or barriers, plenty of models have been proposed. They are Coulomb screening of F pol , 27,28,88) interface flattening realized by establishing wetting conditions provided by Si, 32,[89][90][91] and the change in the band profiles that gives rise to the proper distribution of electron and hole wavefunctions (Y e and Y , h respectively) in the MQWs. 33,92) Particularly for the above-mentioned Al 0.6 Ga 0.4 N/Al 0.75 Ga 0.25 N MQWs, 87,90) Murotani et al 93) have collected important information written in previous literatures, 86,89,90,94) and thought about the reason for the improved NBE PL efficiency of the proper-amount Si-doped wells, as follows.…”
Section: Introductionmentioning
confidence: 99%